BUILDING RESEARCH AND EDUCATIONAL CLUSTER: EXPERIENCE, FEATURES, ADVATAGES - Rais S. Safin; Evgeny A. Korchagin; Ilfak E. Vildanov; Runar N. Abitov; Bulat M. Gareev (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The relevance of the article is defined by the need to improve the quality of training of graduates of educational institutions in a deteriorating economic situation and the reduction of the funding of social programs. According to the authors, under these conditions, a multi-level training in the scientific and educational cluster is more optimal than the traditional, single-level training of students. The experience of the vocational training in civil engineering under the eduational cluster conditions is summarized. The goals of such cluster creation are defined. The features and advantages, in comparison with the conventional education, are defined. On the example of KSUAE scientific-educational cluster reconsideration of approaches to the curricula development are shown. The data over six years is given; concerning training of relative specialties, training at KNAUF company training center, created under the aegis of KSUAE. The article may be useful to scholars, studying vocational training, as well as to future employers, concerned about the quality of graduates.